Verapamil augments carmustine- and irradiation-induced senescence in glioma cells by reducing intracellular reactive oxygen species and calcium ion levels. Issue 5 (April 2017) - Ham, Seok Won; Jeon, Hee-Young; Kim, Hyunggee
Resistance to conventional therapies and frequent recurrence are the major obstacles to the treatment of high-grade gliomas, including glioblastoma. Thus, the development of new therapeutic strategies to overcome these obstacles is necessary to improve the treatment outcomes. In this study, we found that verapamil, a pan–adenosine triphosphate–binding cassette transporter and L-type voltage-dependent calcium channel inhibitor, sensitized U87MG glioma cells to carmustine- and irradiation-induced senescence. Furthermore, our results indicated that verapamil treatment, in combination with carmustine and irradiation, rendered U87MG glioma cells and several patient-derived glioma stem cells more sensitive to therapy-induced senescence than individual or dual-combination treatments. When investigating the underlying mechanism, we found that verapamil treatment markedly decreased intracellular reactive oxygen species and calcium ion levels. Reactive oxygen species reduction with N-acetylcysteine, a reactive oxygen species scavenger, rendered U87MG glioma cells more sensitive to carmustine and irradiation whereas the protein kinase C agonist, phorbol 12-myristate 13-acetate, mitigated the effects of carmustine and irradiation. Taken together, our results indicate that verapamil may be a potent therapeutic sensitizer for increasing the effectiveness of glioblastoma treatment.